Epigenetics of infectious diseases - Doerfler, Walter, 1933-; Casadesús, Josep, 1951- (Springer, 2017)
The present volume of Epigenetics and Human Health is devoted to the patho-epigenetics of viral and microbial infections, an exiting new field of disease-related epigenetic research. As recognized during the past years, epigenetic reprogramming of pathogen and host genome functions - the latter frequently induced by pathogens - plays an important role in many infectious processes. Beyond their immediate relevance for pathogen proliferation and obligatorily associated symptoms, such alterations frequently contribute to severe additional complications, such as the development of immunodeficiency, cancer and various chronic disorders. This holds in particular for epigenetic dysregulation of host gene expression induced by latent infections. The present book summarizes current knowledge of the mechanisms underlying epigenetic changes caused by viral, bacterial, fungal and protozoan infections and their impact on human health.
Keywords: Communicable diseases -- Genetic aspects.; Epigenetics.; elektronické knihy; electronic books